Pengaruh Inovasi Media Paper Plate Terhadap Kemampuan Berhitung Anak Usia 5-6 Tahun - Hilda Nur Fadhilah; Rina Syafrida; Ine Nirmala (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the effect of the use of paper plate media on the numeracy skills of children aged 5-6 years at PAUD Plamboyan 3 Karawang. This study uses quantitative methods with experimental research design with the type of research The one group pretest and posttest, namely research experimentally in one group without any comparison. The data collection techniques in this study used observation methods and data analysis techniques using simple paired t-test. The results of this study indicate that there is a significant effect of paper plate media on children's numeracy skills, with an average pretest score of 58.00 and an average posttest score of 79.31, which means that the value increased significantly. So it can be said that the paper plate media has an effect on children's numeracy skills. It is hoped that this media can be used as a learning medium to develop children's numeracy skills or can be adapted to their needs.